Effects of robotic surgery experience on open radical prostatectomy results: single centre & single surgeon experience - Deniz Gul; Haci Ibrahim Cimen; Yavuz Tarik Atik; Anil Erdik; Burak Uysal; Osman Kose; Hasan Salih Saglam (Scientific Reports)
Abstract This study aimed to evaluate the effect of robotic surgery experience on open radical prostatectomy (ORP) outcomes. We retrospectively reviewed 100 patients who underwent an ORP for clinically localised prostate cancer (PCa) performed by the same experienced surgeon. The groups included the last 50 patients before (Group 1) and the first 50 patients after (Group 2) robotic surgery experience. A detailed history, peroperative, and oncological data were recorded. Continence status and erectile functions were evaluated before surgery and at 1, 3, 6, and 12 months postoperatively by daily pad count and an International Index of Erectile Function (IIEF) short form and were compared between groups. The demographics and preoperative data were similar. The preoperative and postoperative Gleason score was higher in Group 2 (p = 0.001, 0.033; respectively). The operation time (200 vs. 115 min), estimated blood loss (400 vs. 200 ml), peroperative transfusion rate (46% vs. 8%), drain removal time (4 vs. 3 days), hospital stay (5 vs. 4 days), and urethral catheter removal time (21 vs. 14 days) were significantly lower in Group 2 (p < 0.001). The continence rate was significantly higher in Group 2 in the first month (p = 0.027), but no significant difference was found at 3, 6, and 12 months. Erectile functions (mean IIEF: 9.47 vs. 11.18 at 12th month, p = 0.220) showed no significant difference between the groups in the first year after surgery. In addition to ergonomic benefits, robotic surgery provides a significant surgical procedure experience due to its great visualisation. The most important advantages that robotic surgery adds to our ORP experience were improved early continence; less bleeding and a decreased need for transfusions; and a shorter operation time, hospital stay, and urethral catheter removal time.